Extreme Employment Precarity and Health Impacts among South Asians in Toronto - Premji, Stephanie; Begum, Momtaz; Jahangir, Sultana; Gnanayutham, Rachel; McKinnon, John (McMaster University, School of Labour Studies and Geography and Earth Sciences, 2019)
This report describes experiences of extreme employment precarity and impacts on health and well-being among South Asians in Toronto. In 2018, community advocates from the South Asian Women’s Rights Organizations (SAWRO), Injured Workers Community Legal Clinic (IWC), and researchers from McMaster University came together to develop a health and safety workshop for South Asian workers. The initiative grew from a need identified at the community level for more information and advocacy around health and safety in the South Asian community, and among South Asian women in particular. It was funded by a Multicultural Community Capacity Grant from the Government of Ontario. Advocates and researchers developed a 2-hour training workshop on precarious employment, employment rights and workers’ compensation. They trained 10 outreach workers from SAWRO on these topics, and the outreach workers went into their community to share the knowledge they gained and advertise the workshop. The workshop, held in February 2019, was attended by 53 men and women. In March 2019, researchers held two focus groups with a total of 20 South Asian men and women to discuss and document experiences of work and health. This report is ased on the stories shared with us during the training session for outreach workers, the workshop, and the focus groups. --From Introduction